2017
DOI: 10.1177/2325967116680344
|View full text |Cite|
|
Sign up to set email alerts
|

Acute Gastrocnemius-Soleus Complex Injuries in National Football League Athletes

Abstract: Background:Lower extremity muscle injuries are common in professional football. Although less common than hamstring or quadriceps injuries in National Football League (NFL) athletes, calf injuries occur with relative frequency and have not previously been studied.Purpose:To evaluate gastrocnemius-soleus complex muscle injuries over the past 13 years from a single NFL team to determine the incidence of such injuries, their imaging characteristics, and return to play after such injuries and any correlation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 19 publications
2
36
0
Order By: Relevance
“…The rate of same‐season re‐injury has ranged from 4% to 16% . Injury rates in the AFL are comparable to what has been reported in other codes, such as elite soccer and American football …”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…The rate of same‐season re‐injury has ranged from 4% to 16% . Injury rates in the AFL are comparable to what has been reported in other codes, such as elite soccer and American football …”
Section: Introductionsupporting
confidence: 78%
“…Whilst we found gastrocnemius injuries to be less common in AFL players, such injuries appear to be more prevalent in other sports. For example, both Werner et al (investigating American football players) and Koulouris et al (investigating a mixed cohort of people) found gastrocnemius injuries to be more prevalent than soleus injuries. The prevalence of soleus vs gastrocnemius injuries may be somewhat sport‐dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, calf injuries have been studied in NFL players, and 75% were isolated to the gastrocnemius, 15% to the soleus, and 10% to both muscles. 142 The mean time to RTP for calf injuries was 17 days, and 3 players required surgery. Larger fascial defects and the presence of fluid collection on MRI were associated with longer RTP.…”
Section: Resultsmentioning
confidence: 98%
“…A total of 7 studies were identified that investigated the relationship of fascial injury and aspects of RTP (Table 4). 8,12,32,34,35,37,42 However, the applied statistical procedures and the objectives of the conducted analyses in the individual studies were too different to allow meta-analytic pooling of the results.…”
Section: Resultsmentioning
confidence: 99%